Southern European Prospective Investigation Into Childhood Cancer and Nutrition (EPICkids): Study design and protocol - Foteini Perganti; Inge Huybrechts; Adriana Cristina Balduzzi; Ronald Barr; Andrea Biondi; Aina Llenas Bladé; Evangelina Muñoz Bravo; Erika Damasco; Christina N. Katsagoni; Antonis Kattamis; Alvaro Lassaletta; Marta Llopis Lera; et al. (PLoS ONE, 2025)
The survival rates for children with cancer have increased appreciably over the last few decades; however, childhood cancer survivors continue to suffer from long-lasting sequelae. Studies have demonstrated that the presence of malnutrition, over- and under-nutrition, at diagnosis or the duration of malnutrition during treatment is associated with increased toxicity, infection, and inferior survival. Dietary habits, along with behavioral and socioeconomic status, are known factors that lead to obesity or undernutrition and can affect the prognosis and quality of life of children with cancer. Unfortunately, the underlying mechanisms responsible for these observations are largely unknown. To address this gap in science, we established the EPICkids cohort study, an initiative of the International Initiative for Pediatrics and Nutrition at Columbia University Irving Medical Center and the International Agency for Research on Cancer of the World Health Organization. Over a 5-year period, children and adolescents with acute lymphoblastic leukemia and brain tumors receiving treatment in Spain, Italy, or Greece will be recruited. Clinical data and biospecimens (blood and stool) will be collected at designated timepoints in therapy. At the same time, several surveys will be administered to collect data on sociodemographics, physical activity, quality of life, food insecurity, and dietary habits. The primary aim of EPICkids is to develop a large informative nutrition biobank and database to investigate the etiologic pathways that connect nutritional status and lifestyle factors with clinical outcomes in children and adolescents with cancer. Secondary aims are to create evidence-based guidelines for European children with cancer in this understudied region and to ultimately improve the quality of life of those children and adolescents. The ClinicalTrials.gov ID for EPICkids study is NCT05375617.